ANÁLISE DA ASSOCIAÇÃO DE OPERAÇÕES DE CAPITALIZAÇÃO DE PRIVATE EQUITY E VENTURE CAPITAL NO DESEMPENHO DE EMPRESAS COM AÇÕES NA BOVESPA - Domingos, Luis Carlos (2010)
Competitive advantage and organizational performance are both management concepts closely connected to the companies competitiveness and their long-term permanence in the market. In order to reach such goal, according to the RBV foundations, the organizational capabilities of those companies must be dynamic, which means being ahead of the environmental changes, maintaining, creating and developing new capabilities. One of the ways that enables it to happen is the focus on its capitalization, which can be done with the fundraising from third parties or from own resources, with higher or lower degree of risk. Fundraising with third party capital occurs, mainly, through financial institutions and factorings. The fundraising with the use of the companies own resources, can be done through retained earnings or underwriting. The emission made through primary market sets up the initial public offering of shares or Initial Public Offering (IPO). In Brazil, the choice of Private Equity and Venture Capital funds, segments of the financial market that consist mainly of temporary fund raising, has considerably increased in recent years. However, there are only a few academic researches about the use and financial performance that these funds provide to the companies. This study seeks to examine whether companies listed at BOVESPA from 2002 to 2008 and which received funds via Private Equity and Venture Capital with IPO developed superior financial performance than those that received or not other kind of financing in the same period. We selected secondary data such as: balance sheets, profit and shareholder value, using the database Economática. Taking the logarithm of Tobin s Q as dependent variable and log_Ativo, Debt to Equity, ROA, sales raising, investment raising, investment raising Fame and investment raising indebtedness as control variables, statistic tests were used, comparing the average of the indexes, followed by analysis of economic sector, subsector and follow up. The result shows that the companies that received funds through Private Equity and Venture Capital with IPO became different from other companies that were listed at BOVESPA in that period. The present paper aims to contribute to the enrichment of academic knowledge towards this issue.(AU)